The Judge’s Consideration on Decisions on Custody of Minor Children on The Father’s Maqasid Syariah Perspective Jamaluddin Athiyyah - Rendra Muhammat; Bakhouya Driss (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This research is motivated by divorces carried out by married couples for various reasons. After the decision is granted, the panel of judges will provide various considerations regarding child custody. According to Indonesian law, obtaining child custody must be pursued through litigation to ensure legal certainty. Both parents, whether fathers or mothers, have an equal opportunity to claim custody and obtain a determination of child custody. Child custody requests can be included in a divorce or divorce lawsuit or filed separately. This research used a qualitative approach with a normative legal research type. The data used in this study are data from library research. The primary data sources in this study are legal materials: Decision Number 2075/Pdt.G/2023 PA Kab. Kdr. Data analysis through editing, systematization, description, and concluding. The results of the study show that (1) Decisions regarding custody of minor children on fathers at the Religious Court of Kediri Regency in 2023, namely number 2075/Pdt.G/2023/PA.Kab.Kdr. based on agreement, the mother has bad behavior, and financial capabilities, and understands the emotional and psychological needs of the child, (2) The judge’s considerations in the decision regarding the father’s custody of a minor child are reviewed from the perspective of Maqasid Syariah Jamaluddin Athiyah, namely that the basis of the judge’s considerations is in accordance with Maqashid Syariah at the dharuriyat level (primary decision), Maqashidus Syari’ah Fiimaa Yata’alaqu Bil Usroh (family scope) in the Tandhimil Jaanibil Maalii Lil Usroh section (protection of family finances), and Tandhimil Jaanibil Muasisi Lil Usroh (strengthening relationships between family members).